Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.32479/ijeep.13263
|View full text |Cite
|
Sign up to set email alerts
|

The International Gas and Crude Oil Price Variability Effect on Indonesian Coal Mining Companies Listed at IDX

Abstract: This study investigates the influence of gas price, crude oil price and international coal demand on coal sales volume, coal selling price, coal sales revenue, financial performance, business risk and stock price Indonesia coal mining is listed on Indonesia Stock Exchange (IDX). The sample is Indonesia coal mining companies listed on IDX in the period 2014 – 2018. This study employs a structural equation model using GeSCA software to examine the relationship and effect between research variables. The empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…The data on industrial production are primarily provided by the Czech Statistical Office, they are called the monthly and quarterly basic index of industrial production, respectively. The inclusion of these variables can be observed in works of Adi (2022), Ji et al (2019), Mo et al (2012). As electricity, natural gas and emission permits are priced in euro, we also use the series of EUR/CZK spot exchange rate 1 to convert these series into corresponding series in CZK.…”
Section: Datamentioning
confidence: 99%
“…The data on industrial production are primarily provided by the Czech Statistical Office, they are called the monthly and quarterly basic index of industrial production, respectively. The inclusion of these variables can be observed in works of Adi (2022), Ji et al (2019), Mo et al (2012). As electricity, natural gas and emission permits are priced in euro, we also use the series of EUR/CZK spot exchange rate 1 to convert these series into corresponding series in CZK.…”
Section: Datamentioning
confidence: 99%
“…Fuel price increase sensitivity impact of a 50% increase in fuel price in generating cost is 3% on Nuclear Power Plants, 20% on Integrated (Brook et al, 2014). Gas Price has a significant negative effect on International Coal Demand, bidirectionally (Adi, 2022). Linn and Muehlenbachs (2018) found that low natural gas prices increase gas-fired electricity generation, reduce coalfired electricity generation, and reduce wholesale electricity prices.…”
Section: Fossil Fuel Price Nuclear Energy Generation and Comentioning
confidence: 99%